A European Perspective in Academic Mobility: A Case of Erasmus Program - Mizikaci, Fatma; Arslan, Zülal Ugur (Journal of International Students, 2019)
ERASMUS is a mobility program that provides its participants with experiences in their fields of study and work by presenting them global trends. It promotes the academic, professional and individual development of the participants while contributing to the extension of the worldwide work market. This study aims to explore the impact of the Erasmus Program from the perspectives of Turkish students. Twelve Erasmus students in different fields of study at three universities in Ankara were interviewed. Findings were analyzed into the themes of individual, professional and academic development, future of careers and global work market development. It is concluded that Erasmus has an impact on not only individuals but also on the worldwide labor market with its enlarging scope and comprehensive strategies as well as its challenges by rapid developments in the demands and needs of the new era.